ANALISIS PEMANFAATAN RUANG PUBLIK PADA AKTIVITAS PENDUDUK DI PERMUKIMAN STUDI KASUS : PERMUKIMAN MLATEN KOTA SEMARANG - Anggita Nur Zahara Mariza; Ardiana Yuli Puspitasari (Jurnal Planologi, 2017)
Mlaten settlement is one of the old neighborhoods in the city of Semarang that arrangement very concerned about the existence of a public space. The neighborhood was designed by Thomas Karsten in 1994 for low-income people with the design concept of "Garden City" which is very attentive to the good order of settlement patterns with emphasis on the existence of public space in the form of neighborhood parks and roads are equipped with a boulevard. Currently Mlaten settlements have become congested, the existence of public spaces began to have a variety of activities. The diversity of activities and multifunctional use of public space in residential Mlaten today shows the importance of public space as well as irregularities in the use of public space. Therefore, the study will be assessed linkage activities of people in the Settlement Mlaten to use public space to form their utilization patterns.The approach taken in this research using qualitative methods rationalistic approach. The analytical tool used is the 'behavioral mapping' to obtain information about the behavior, activities of individuals and groups associated with spatial systems through analysis of activity patterns and forms of space utilization.The conclusion from this study is the public space in Settlement Mlaten into a multifunctional space to support the activities of citizens outside the residential space, public space is not only a space that is used for public purposes, but also to meet the needs of personal citizens such as the emergence of a drying, parking, and put the used goods or merchandise that occur in public spaces. The pattern of use of public space in Settlement Mlaten showed a pattern that tends to accumulate at the edge of the garden or in the middle of the boulevard road to activities that are personal as drying/ washing, parking, putting the former home goods. While gathering or spreading pattern is happening on the utilization of public activity people like child's play, sports, or just sitting.Keywords: Settlement, Utilization Patterns, Public Space, and Activities.